Sudden Stops and Currency Drops : A Historical Look - Catao, Luis (IMF Working Papers; Working Paper ;, 2006)
This paper shows that recent manifestations of sudden stops (SSs) in international capital flows have striking parallels in the early financial globalization era preceding World War I. All main capital-importing countries then faced episodic capital flow reversals averaging some 5 percent of GDP and with a median duration of four years. Most SSs also displayed striking crosscountry synchronization, being immediately preceded by rising world interest rates. Both fixed and floating exchange rate regimes were hit, with no significant differences between them. Yet, not all SSs resulted in currency drops: while some countries experienced currency collapses, others managed to preserve exchange rate stability. These different responses are related to domestic "frictions" that heightened the procyclicality of absorption and hindered precautionary reserve accumulation in some countries relative to others.